Analisis Hubungan Ekspor, Pembayaran Hutang Luar Negeri Dan Nilai Tukar Terhadap Cadangan Devisa Indonesia - Fakhrurrazi Fakhrurrazi; Hijri Juliansyah (JURNAL EKONOMIKA INDONESIA, 2021)
This study aims to determine the relationship between exports, foreign debt payments, and the exchange rates on the foreign exchange reserves of Indonesia in 1988-2019. This study uses secondary data for 31 years and uses the Autoregressive Distributed Lag (ARDL) analysis method to analyze the data. The results of this study indicate that all variables have no relationship between variables, only on the foreign exchange reserves to exports. In short-term testing, the export does not have a significant effect on foreign exchange reserves, and the foreign debt payment and the exchange rate have a significant effect on foreign exchange reserves. However, in the long run, all variables do not have a significant effect on foreign exchange reserves.Keywords:Exports, Foreign Debt Payment, Exchange Rates, Foreign Exchange                    Reserves, ARDL